Degradation of metronidazole by radio frequency discharge in an aqueous solution. Issue 4 (8th December 2017) - Wang, Lei; Wang, Jinxiu; Lin, Junxin; Zhang, Songlin; Liu, Yongjun
Abstract : Degradation of metronidazole (MNZ) by radio frequency discharge in water was examined. Results showed that OH, H, and O were produced. Decay of MNZ followed pseudo‐first order kinetics, where the apparent rate constant was independent of its initial concentration in the range 0–0.5 mM, decreased in the range 0.5–1.0 mM, and leveled off in the range higher than 1.0 mM. pH had no effects on MNZ degradation. OH scavengers enhanced the MNZ removal. Formic acid, nitrite ion, oxalic acid, nitrate ion, and acetic acid were determined as the primary intermediate byproducts. The eventual products were ammonia and inorganic carbon. Both OH and H participated in the MNZ degradation. H played more efficient role than OH in the early stage. Abstract : Complete mineralization of aqueous metronidazole induced by radio frequency discharge in water has been achieved. OH, H, and O were produced. Decay of MNZ followed pseudo‐first order kinetics, and no pH effects were observed. OH scavengers enhanced the removal. Formic acid, nitrite ion, oxalic acid, nitrate ion, and acetic acid were the major intermediate byproducts. Final products were ammonia and inorganic carbon. Both OH and H participated in the MNZ degradation.